The Influence of Experiential Marketing and Promotion on Consumer Loyalty at KFC Centre Point Medan Fast Food - William, Chelsea; Ying, Teo Yin; Annastasia, Fionna (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the effect of experiential marketing and promotion on consumer loyalty at KFC Centre Point Medan. Using a descriptive quantitative method with a questionnaire survey of 96 consumers, results reveal that experiential marketing and promotion simultaneously have a significant effect on loyalty. Partially, act marketing, relate marketing, and promotion have positive and significant impacts, while sense, feel, and think marketing do not. These findings indicate that KFC should focus on strengthening act and relate marketing strategies alongside effective promotional activities to enhance consumer loyalty and maintain competitiveness in the fast-food industry, providing valuable insights for business marketing planning.